Model Pembelajaran PAI Sekolah Dasar di Masa Pandemi Covid-19 - Achmad Maulidi; Ali Tohir; Wirdaturrahmah Wirdaturrahmah; Moh. Wardi; Musleh Musleh (Maharot : Journal of Islamic Education, 2021)
The disruption era has become clearer after Indonesia experienced the Covid 19 emergency, especially in the education and learning process. The purpose of this research is to find out how the Islamic education learning model for elementary schools is during the Covid-19 pandemic. The second is to find out the obstacles faced by schools in the implementation of learning during the Covid-19 pandemic. This research is a qualitative case study approach. The data were obtained from the principal, teachers, parents and students using non-participant observation techniques, interviews and documentation. Meanwhile, to analyze the data used data presentation data reduction and drawing conclusions. The results of this study indicate that the learning process for elementary school PAI during the Covid pandemic was not optimal, one of the factors was due to the fact that the pattern had not prepared concrete regulations or policies for the implementation of learning during the Covid pandemic. The obstacles faced were related to general conditions that had not ready to learn during the pandemic.